The bronchial epithelial cell bacterial microbiome and host response in patients infected with human immunodeficiency virus. Issue 1 (December 2016) - Sze, Marc; Xu, Stella; Leung, Janice; Vucic, Emily; Shaipanich, Tawimas; Moghadam, Aida; Harris, Marianne; Guillemi, Silvia; Sinha, Sunita; Nislow, Corey; Murphy, Darra; Hague, Cameron; et al.
Abstract Background Chronic Obstructive Pulmonary Disease (COPD) is an important comorbidity in patients living with human immunodeficiency virus (HIV). Previous bacterial microbiome studies have shown increased abundance of specific bacterium, likeTropheryma whipplei, and no overall community differences. However, the host response to the lung microbiome is unknown in patients infected with HIV. Methods Two bronchial brush samples were obtained from 21 HIV-infected patients. One brush was used for bacterial microbiome analysis using the Illumina MiSeqTM platform, while the other was used to evaluate gene expression patterns of the host using the Affymetrix Human Gene ST 2.0 array. Weighted gene co-expression network analysis was used to determine the relationship between the bacterial microbiome and host gene expression response. Results The Shannon Diversity was inversely related to only one gene expression module (p = 0.02); whereas evenness correlated with five different modules (p ≤ 0.05). After FDR correction only the Firmicutes phylum was significantly correlated with any modules (FDR < 0.05). These modules were enriched for cilia, transcription regulation, and immune response. Specific operational taxonomic units (OTUs), such as OTU4 (Pasteurellaceae), were able to distinguish HIV patients with and without COPD and severe emphysema. Conclusion These data support the hypothesis that the bacterial microbiome in HIV lungs is associated with specific host immune responses. Whether or not these responses are also seen in non-HIV infected individuals needs to be addressed in future studies.